Reorganization of public procurement of biosimilars and its economic effect on the monoclonal antibody market in Russia - A. Yu. Efremov; A. M. Vlasov; V. I. Gegechkori; N. V. Gorpinchenko; G. V. Ramenskaya; T. M. Litvinova (Фармакоэкономика, 2025)
Background. The increasing number of registered biosimilars of monoclonal antibodies (mAbs) is altering the structure of the pharmaceutical market by amplifying the share of domestic manufacturers. Therefore, investigating their economic effect appears highly relevant.Objective: To examine the impact of biosimilars on the market for public procurement of medicinal products based mAbs during the period 2022–2023.Material and methods. A list of registered drugs based on mAbs was compiled from the State Register of Medicines and the Unified Information System for Procurement databases. The study involved statistical and marketing methods, including normalization of drug costs to weighted average prices (rub/mg), ABC analysis to identify key positions based on expenditure, and competitive analysis to categorize drugs as either original or biosimilars.Results. The analysis of weighted average prices for original drugs and biosimilars, as well as their procurement volumes, demonstrated a significant economic effect on the health care system. The greatest savings were achieved through the procurement of bevacizumab and pembrolizumab biosimilars, resulting in savings of 15.1 and 3.8 billion rubles, respectively. In the group of rituximab drugs, procurement of biosimilars led to savings of approximately 2 billion rubles.Conclusion. The introduction of biosimilars into the public procurement market has significantly optimized costs, thereby increasing patient access to life-saving medicines. The results emphasize the necessity for further development of biosimilars market to enhance the efficiency of public procurement and improve drug accessibility. However, a comprehensive understanding of their economic advantages require clinical studies that confirm the efficacy and safety of biosimilars in real-world clinical practice.